STUDENT PREFERENCE TO USE QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) AS A DIGITAL PAYMENT INSTRUMENT - Shintaro, Margareta; Bhirawa, Sigit Wisnu Setya (MSJ : Majority Science Journal, 2024)
Technological developments result in innovations in financial services called financial technology (fintech). The result of fintech development is the existence of QRIS (Quick Response Code Indonesian Standard) as an easy and practical digital payment system. QRIS attracts the attention of young people, namely students, to switch from cash to non-cash payments with QRIS. The problem in this study is how students prefer to use QRIS as a digital payment tool? is the seller involved in students' preferences in using QRIS as a digital payment tool? To answer this problem, researchers used a qualitative approach by collecting data through interviews with three types of informants, namely sellers, students who make cash payments, and students who make cash payments, and students who make payments with QRIS. The result of this study is that students' preferences in using QRIS depend on ingrained payment habits in the canteen. However, even so, the preference for QRIS convenience can support the efficiency of buying and selling transactions in canteens.